1999
DOI: 10.3138/jcfs.30.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Marriage in Sweden: Immigration and Assimilation 1971-1993

Abstract: Sweden, once considered a nation of emigration, has experienced a great deal of immigration and is now a multi-ethnic state. National data on marriages performed in Sweden between 1971 and 1993 are examined to analyze the rates and patterns of cross-national unions. Comparisons are made between Swedish men and women in their tendency to intermarry with particular nationalities over time. These intermarriage trends and patterns are discussed in relation to data on immigration to Sweden during approximately the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Binational marriages have not been studied extensively in Sweden. Cretser () examined cross‐national marriages, defining citizens as natives and non‐citizens as foreigners, for the period 1971–1993 and observed that the number of these marriages had significantly increased over time. During the two decades of Cretser's study, most foreign partners originated from the Nordic countries, but marriages with non‐Nordic spouses were on the rise.…”
Section: Binational Marriages In Swedenmentioning
confidence: 99%
See 1 more Smart Citation
“…Binational marriages have not been studied extensively in Sweden. Cretser () examined cross‐national marriages, defining citizens as natives and non‐citizens as foreigners, for the period 1971–1993 and observed that the number of these marriages had significantly increased over time. During the two decades of Cretser's study, most foreign partners originated from the Nordic countries, but marriages with non‐Nordic spouses were on the rise.…”
Section: Binational Marriages In Swedenmentioning
confidence: 99%
“…Previous studies have shown that intermarriages, or marriages between natives and migrants, increased significantly in Sweden from the 1970s to the 1990s (Cretser, ). Marriages with non‐Nordic spouses were found to be on the rise, especially marriages with marriage migrants (Niedomysl et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Mostly former mixed marriage investigations have particularly been concerned on analysing the level of assimilation into host societies between non-skilled migrants when married to native citizens, and they hardly had drawn from a theoretical insight focused on the social consequences of EU mobility (see, for example, Cortina et al 2008;Cretser 1999;González Ferrer 2006;Lievens 1999;Neyrand and M'Sili 1998;Kalmijn and van Tubergen 2006;Klein 2001;Rodríguez García 2006;Rother 2008;van Tubergen and Maas 2007). Therefore, this paper has attempted to overcome this absence by presenting an empirical contribution on the assessment of mixed marriages between highly educated European free-movers.…”
Section: Resultsmentioning
confidence: 99%
“…However, with some exceptions, mostly based on case studies and statistical data (Varro 1995;Lauth Bacas 2002;Block 2007;Braun and Recchi 2008;Gaspar 2008;2009a;Santacreu Fernández and García 2008;Scott and Cartledge 2009), this idea has barely been investigated. Most studies that have focused on mixed marriages in Europe have centred on unions between European natives and guest workers (both European and non-European) (Cortina et al 2008;Cretser 1999;Gonzaléz Ferrer 2006;Lievens 1999;Neyrand and M'Sili 1998;Kalmijn and Van Tubergen 2006;Klein 2001;Rodríguez García 2006;Rother 2008;Van Tubergen and Maas 2007), in order to evaluate the degree of social integration or assimilation of these communities when living in their countries of destination.…”
Section: On the Assessment Of European Intra-marriagementioning
confidence: 99%
“…intimate relationships with people from Finland, the UK, Norway, and Germany (Lange and Westin, 1997). The statistics on intermarriage among SWE seems to reflect these attitudes, since most of the intermarriage involves someone of SC and Western European background (Cretser, 1999;Stenflo, 2001). Larger number of respondents being positive toward CEEs and LAs concurs with previous general attitude surveys in Sweden, which show that they are perceived to be culturally closer to SWE compared to SEA, A, and ME (Lange and Westin, 1997;Mella and Palm, 2010).…”
Section: Different Attitudes Toward Different Groupsmentioning
confidence: 97%